Process for the preparation of a catalyst for the oxidation of fischer-tropsch waxes and use thereof

CN122912913APending Publication Date: 2026-10-16ZIBO HEYI FINE CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611399642.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]现有费托蜡氧化工艺多采用常规金属盐类催化剂开展氧化反应,这类催化剂在熔融蜡体体系中分散能力有限,金属活性组分容易发生聚集,造成催化活性下降,反应过程易产生大量副产物,反应结束之后,金属盐催化剂难以从蜡质产物体系中实现高效分离,催化剂组分容易残留在氧化费托蜡内部,提升产物灰分水平,影响最终产品质量,大部分现有催化体系不具备便捷回收复用的能力,催化剂只能单次投入使用,造成物料消耗增加,抬高整体生产成本,部分工艺为除去残留催化剂,需要增设多道精制除杂工序,增加生产设备投入,延长工艺流程,部分改性方案反应条件苛刻,反应过程可控性差,不同批次产出的氧化费托蜡性能指标波动明显,难以满足工业化稳定生产的实际需求

Benefits of technology

[0021] I. This invention utilizes imidazole bromide and cobalt acetate to construct an ionic liquid coordination catalyst, thereby altering the microscopic coordination environment of the metal active centers. This allows the active metal components to be uniformly dispersed within the ionic liquid matrix, preventing agglomeration and deactivation of the active metal sites. The catalyst achieves excellent dispersion in the Fischer-Tropsch wax molten system, and a relatively low catalyst addition is sufficient to drive the stable Fischer-Tropsch wax oxidation process. This reduces the introduction of foreign impurities into the oxidation products. After the reaction, temperature control enables phase separation between the catalyst and the product system, and centrifugation can be used to recover the catalyst. The recovered catalyst can be reused in the oxidation reaction, reducing catalyst material consumption. The entire process eliminates the need for complex post-treatment and impurity removal procedures, reducing product quality fluctuations caused by additive residues. It is suitable for the production process of Fischer-Tropsch wax oxidation to prepare oxidized Fischer-Tropsch wax, simplifying the overall production process and controlling production material costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912913A_ABST
    Figure CN122912913A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method and application of a Fischer-Tropsch wax oxidation reaction catalyst, relates to the technical field of Fischer-Tropsch wax deep processing and catalytic materials, and specifically comprises the following steps: 1-dodecyl-3-methyl imidazole bromide is dissolved in anhydrous ethanol, and under nitrogen protection, cobalt acetate is added in batches according to a molar ratio of 2.05:1, a mixture is obtained by reacting at 60 DEG C for 6h; the imidazole-cobalt ionic liquid coordination catalyst is prepared by performing vacuum distillation, washing with n-hexane and drying; Fischer-Tropsch wax is melted, a small amount of the catalyst is added, and air is introduced, 4h of oxidation reaction is carried out at 145 DEG C, after the reaction, crystallization is carried out by cooling, the catalyst is recovered by centrifugation, and the catalyst can be recycled after drying; the imidazole-cobalt coordination catalyst prepared by the application can inhibit metal agglomeration, catalyze Fischer-Tropsch wax oxidation with a low catalyst dosage, the catalyst can be recycled, the process is optimized, the reaction condition is optimized, side reactions are inhibited, product indexes are stable, the cost is reduced, and the application is suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of Fischer-Tropsch wax deep processing and catalytic materials technology, specifically to the preparation method and application of catalysts for Fischer-Tropsch wax oxidation reactions. Background Technology

[0002] Fischer-Tropsch wax is a solid hydrocarbon mixture produced by coal-to-oil processes, mainly composed of saturated long-chain alkanes. It possesses the basic characteristics of high purity and low sulfur and nitrogen impurities. However, in its original state, the molecule lacks polar functional groups, significantly limiting its direct applications. To broaden the application range of Fischer-Tropsch wax, the industry commonly introduces polar groups such as carboxyl groups onto the alkane molecular chain through oxidation modification, resulting in oxidized Fischer-Tropsch wax products. Oxidized Fischer-Tropsch wax exhibits good emulsification ability and compatibility, making it highly valuable in many industrial fields such as plastics processing, coating additives, and lubricants. The oxidation reaction of Fischer-Tropsch wax mostly relies on catalytic oxidation, and the performance of the catalyst directly determines the reaction efficiency and product quality. Ionic liquid coordination catalytic systems, with their tunable structure and excellent solubility, are gradually gaining attention in the field of hydrocarbon oxidation modification. Combining ionic liquids with transition metals to construct catalytic systems provides a new technical path for the efficient oxidation modification of Fischer-Tropsch wax and has become an important direction for technological research in the industry.

[0003] Existing Fischer-Tropsch wax oxidation processes mostly employ conventional metal salt catalysts. These catalysts have limited dispersion in molten wax systems, and the active metal components tend to aggregate, leading to decreased catalytic activity. The reaction process also generates a large number of byproducts. After the reaction, the metal salt catalyst is difficult to separate efficiently from the wax product system, and catalyst components tend to remain inside the oxidized Fischer-Tropsch wax, increasing the ash content of the product and affecting the quality of the final product. Most existing catalytic systems lack convenient recycling and reuse capabilities, and the catalyst can only be used once, resulting in increased material consumption and higher overall production costs. Some processes require multiple refining and impurity removal steps to remove residual catalysts, increasing investment in production equipment and extending the process flow. Some modification schemes have harsh reaction conditions, poor controllability of the reaction process, and significant fluctuations in the performance indicators of oxidized Fischer-Tropsch wax produced in different batches, making it difficult to meet the actual needs of stable industrial production. Summary of the Invention

[0004] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a method for preparing and applying a catalyst for the oxidation reaction of Fischer-Tropsch wax. This method uses imidazole bromide and cobalt acetate as raw materials to synthesize an imidazole-cobalt ionic liquid coordination catalyst in an anhydrous ethanol system under nitrogen protection. The catalyst is then obtained through vacuum distillation, solvent washing, and drying. The resulting catalyst is added to molten Fischer-Tropsch wax, and air is introduced for catalytic oxidation. After the reaction is complete, the catalyst is recovered and dried by cooling crystallization and centrifugation, allowing it to be recycled for further oxidation reactions. The catalyst prepared by this invention has good dispersibility, requires a low dosage, reduces impurity introduction, and minimizes material consumption. It also includes a complete preparation and process control flow to suppress side reactions, ensure stable product indicators, and simplify post-processing. This method is suitable for the industrial preparation of oxidized Fischer-Tropsch wax and enhances the economic value of deep processing of Fischer-Tropsch wax.

[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution: On the one hand, a method for preparing a catalyst for the Fischer-Tropsch wax oxidation reaction, the specific steps of which are as follows:

[0006] S1. Dissolve 1-dodecyl-3-methylimidazolium bromide in anhydrous ethanol. Under nitrogen protection, add cobalt acetate in batches according to a molar ratio of 1-dodecyl-3-methylimidazolium bromide to cobalt acetate of 2.05:1. Maintain the system under a slightly positive pressure throughout the reaction process and stir at 55~65℃ for 4~8 hours to obtain a mixture.

[0007] S2. The mixture is subjected to vacuum distillation at -0.085~-0.095MPa and 55~65℃ to obtain a crude imidazole-cobalt ion liquid coordination catalyst.

[0008] S3. Add n-hexane to the crude catalyst for washing and separation, repeat washing until the UV detection endpoint, and dry at 40~50℃ to obtain imidazole-cobalt ion liquid coordination catalyst.

[0009] S4. Melt Fischer-Tropsch wax at 120~130℃, add the catalyst at 0.02~0.06% of the mass of Fischer-Tropsch wax, introduce air under stirring, and react at 140~150℃ for 3~5 hours;

[0010] S5. After the reaction is complete, stop the gas supply, cool down to crystallize, and centrifuge to recover the catalyst. Dry the recovered catalyst and reuse it for subsequent oxidation reactions.

[0011] Further, 800-1000 mL of anhydrous ethanol is added per mole of 1-dodecyl-3-methylimidazolium bromide, the stirring rate is set to 200-300 r / min, and the stirring time is 20-30 min; the cobalt acetate is added to the system in 3 to 5 batches, with an interval of 5-8 min between adjacent additions; the system heating rate is controlled at 2-3 °C / min, and the stirring rate is set to 250-350 r / min during the isothermal reaction stage.

[0012] Furthermore, the nitrogen protection system maintains a slightly positive pressure, with a pressure range of 0.01~0.03MPa, a nitrogen flow rate of 0.5L / min, and a nitrogen purging operation lasting 15min.

[0013] Furthermore, in S2, the stirring rate during the entire vacuum distillation process is set to 150~200 r / min; when the volume of distillate flowing out every 10 minutes is less than 1 mL and the total mass fraction of ethanol and acetic acid in the distillate is less than 0.5%, the vacuum distillation is terminated; the maximum temperature of the material during the vacuum distillation process does not exceed 70℃.

[0014] Furthermore, in step S3, the crude catalyst and n-hexane are fed at a mass-to-volume ratio of 1:3 to 1:5 g / mL; the stirring rate for each wash is 200 to 300 r / min, the stirring time is 15 to 20 min, and the settling time is 20 to 30 min; the washing operation is repeated 3 to 5 times, and the ultraviolet detection signal is collected at a wavelength of 211 nm. The washing endpoint is determined when the absorbance is lower than 0.02; the vacuum degree during the drying process is not lower than -0.095 MPa, and samples are taken every 30 min. The drying process ends when the residual mass fraction of n-hexane in the material is lower than 0.1%.

[0015] Furthermore, in step S3, a trace amount of nitrogen is continuously introduced during the drying stage, and the nitrogen comes into contact with the material in the same direction.

[0016] Furthermore, in step S4, the stirring speed during the Fischer-Tropsch wax melting stage is set to 150-200 r / min; after the catalyst is fed, the stirring speed is increased to 300-400 r / min, and the stirring time is 10-15 min; the introduced air is sequentially treated by silica gel adsorption and activated carbon adsorption; the air introduction rate is 0.3-0.5 L of standard state air per kilogram of Fischer-Tropsch wax per minute; the system heating rate is 1-2℃ / min, and the reaction temperature fluctuation range is 145℃±2℃.

[0017] Furthermore, in S5, the cooling crystallization operation temperature is controlled at 60~80℃; the drying temperature of the recovered catalyst is not higher than 100℃.

[0018] Furthermore, in S5, the recovered catalyst is used for subsequent multiple rounds of repeated oxidation reactions, and product samples are collected periodically to record the acid value, ash content, and clay consumption values ​​of each round of samples in order to monitor catalyst activity.

[0019] On the other hand, there is the application of a method for preparing a catalyst for the Fischer-Tropsch wax oxidation reaction, which is used to prepare oxidized Fischer-Tropsch wax products by Fischer-Tropsch wax oxidation.

[0020] Compared with existing technologies, the preparation method and application of this catalyst for the Fischer-Tropsch wax oxidation reaction have the following advantages:

[0021] I. This invention utilizes imidazole bromide and cobalt acetate to construct an ionic liquid coordination catalyst, thereby altering the microscopic coordination environment of the metal active centers. This allows the active metal components to be uniformly dispersed within the ionic liquid matrix, preventing agglomeration and deactivation of the active metal sites. The catalyst achieves excellent dispersion in the Fischer-Tropsch wax molten system, and a relatively low catalyst addition is sufficient to drive the stable Fischer-Tropsch wax oxidation process. This reduces the introduction of foreign impurities into the oxidation products. After the reaction, temperature control enables phase separation between the catalyst and the product system, and centrifugation can be used to recover the catalyst. The recovered catalyst can be reused in the oxidation reaction, reducing catalyst material consumption. The entire process eliminates the need for complex post-treatment and impurity removal procedures, reducing product quality fluctuations caused by additive residues. It is suitable for the production process of Fischer-Tropsch wax oxidation to prepare oxidized Fischer-Tropsch wax, simplifying the overall production process and controlling production material costs.

[0022] II. This invention effectively removes residual solvents and unreacted raw material impurities during the catalyst preparation process by controlling the atmosphere, solvent removal, and washing and purification processes. This improves the purity of the catalyst itself, reduces the induction of side reactions in the oxidation of Fischer-Tropsch wax by impurities, and directs the oxidation reaction towards the target product. Air feedstock participates in the reaction after pretreatment, reducing the interference of impurities introduced by the gas on the reaction system. The temperature and transport conditions during the reaction process are controlled in a coordinated manner to ensure the stability and controllability of the oxidation reaction process. The catalyst recovery and reuse process is accompanied by multiple sets of parallel tests to verify the performance of recycling. This allows for a direct understanding of the changes in various indicators of the product under recycling conditions, facilitating timely evaluation of the catalyst's usage status and ensuring the stability of indicators of multiple batches of Fischer-Tropsch wax products, providing reliable support for large-scale continuous production.

[0023] Other advantages, objectives and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination or study, or may be learned from the practice of the invention. Attached Figure Description

[0024] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are merely some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without any creative effort.

[0025] Figure 1 Flowchart of the preparation of imidazole-cobalt ionic liquid coordination catalyst and Fischer-Tropsch wax oxidation process;

[0026] Figure 2 Bar chart showing the effect of different molar ratios of 1-dodecyl-3-methylimidazolium bromide to cobalt acetate on the properties of Fischer-Tropsch wax oxidized products;

[0027] Figure 3 Line graph showing the effect of different catalyst dosages on the properties of Fischer-Tropsch wax oxidation products;

[0028] Figure 4 Line graph showing the effect of different air intake rates on the properties of Fischer-Tropsch oxidized wax products;

[0029] Figure 5 A bar chart showing the effect of different cooling crystallization temperatures on catalyst recovery and the acid value of oxidation products. Detailed Implementation

[0030] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with the accompanying drawings and preferred embodiments, is provided below.

[0031] Example 1:

[0032] Take 1-dodecyl-3-methylimidazolium bromide and add anhydrous ethanol at a ratio of 900 mL anhydrous ethanol per mole of 1-dodecyl-3-methylimidazolium bromide. Set the stirring speed to 250 r / min and stir continuously for 25 min until the 1-dodecyl-3-methylimidazolium bromide is completely dissolved. Set up a nitrogen protection pipeline and perform nitrogen purging for 15 min, maintaining a slightly positive pressure range of 0.01~0.03 MPa, with a nitrogen flow rate of 0.5 L / min. According to the molar ratio of 1-dodecyl-3-methylimidazolium bromide to cobalt acetate of 2.05:1, divide cobalt acetate into four portions and add them sequentially to the reaction system, with a 6 min interval between each addition. Control the system temperature rise rate at 2.5℃ / min, raise the temperature to 60℃, and set the stirring speed to 300 r / min during the isothermal reaction stage. Continue stirring for 6 h to obtain a mixture. Figure 1 As shown.

[0033] The resulting mixture was transferred to a vacuum distillation apparatus. The stirring rate was set to 180 r / min throughout the distillation process, the vacuum level was controlled at -0.090 MPa, and the distillation temperature was 60℃. The maximum temperature of the material during the vacuum distillation process did not exceed 70℃. The distillate was continuously collected. When the outflow volume was less than 1 mL every 10 minutes and the total mass fraction of ethanol and acetic acid in the distillate was below 0.5%, the vacuum distillation operation was terminated, yielding a crude imidazole-cobalt ionic liquid coordination catalyst.

[0034] The crude catalyst was fed with n-hexane at a mass-to-volume ratio of 1:4 g / mL. A single wash was performed with a stirring rate of 250 rpm for 18 min, followed by a settling period of 25 min to separate the lower layer. The washing process was repeated four times. UV detection was performed at 211 nm, and the wash endpoint was defined as an absorbance below 0.02. The washed material was then transferred to a vacuum dryer. The vacuum level was maintained at -0.095 MPa, and the drying temperature was set to 45°C. A trace amount of nitrogen was continuously introduced during the drying process, with the nitrogen in contact with the material in the same direction. Samples were taken every 30 min, and drying was stopped when the residual mass fraction of n-hexane in the material fell below 0.1%, yielding the imidazole-cobalt ionic liquid coordination catalyst.

[0035] A measured amount of Fischer-Tropsch wax was added to the reactor. During the melting stage, the stirring speed was set to 180 r / min, and the temperature was raised to 125℃ to ensure complete melting of the Fischer-Tropsch wax. 0.04% (by mass) of imidazole-cobalt ionic liquid coordination catalyst was added. After the catalyst was added, the stirring speed was increased to 350 r / min, and the stirring time was 12 min. The introduced air was sequentially treated by silica gel adsorption and activated carbon adsorption, with an air flow rate of 0.4 L of standard-condition air per kilogram of Fischer-Tropsch wax per minute. The system was heated at a rate of 1.5℃ / min, reaching 145℃. The temperature fluctuation range of the system was controlled within 145℃ ± 2℃, and the reaction was continuously stirred for 4 h.

[0036] After the reaction is complete, stop the gas supply, cool down and crystallize at 70°C to complete the crystallization process, centrifuge to recover the catalyst, and dry the recovered catalyst at a temperature not exceeding 100°C. The dried catalyst is then directly fed into the next round of oxidation reaction.

[0037] Three parallel samples were set up for each catalyst recovery, and five to ten parallel oxidation experiments were carried out continuously. Product samples were collected for each round of repeated oxidation experiments, and the acid value, ash content and clay consumption of each sample were recorded. The repeated oxidation experiments were conducted for a maximum of two rounds.

[0038] Example 2:

[0039] Optimization of raw material molar ratio conditions in stage S1:

[0040] Preparation of imidazole-cobalt ionic liquid coordination catalysts with different molar ratios:

[0041] In the catalyst preparation stage S1, all other process parameters were kept constant, except for the molar ratio of 1-dodecyl-3-methylimidazolium bromide to cobalt acetate. All three ratios were within the process limits, and three experimental conditions (2.00:1, 2.05:1, and 2.10:1) were set for catalyst preparation. In each experiment, when dissolving 1-dodecyl-3-methylimidazolium bromide, 900 mL of anhydrous ethanol was added per mole of 1-dodecyl-3-methylimidazolium bromide. The stirring rate was set to 250 r / min, and the stirring time was 25 min. Nitrogen purging was performed for 15 min at a flow rate of 0.5 L / min, maintaining a slightly positive pressure range of 0.01–0.03 MPa. Cobalt acetate was added to the system in four equal portions, with a 6-min interval between each addition. The system heating rate was controlled at 2.5 °C / min, reaching 60 °C. During the isothermal reaction stage, the stirring rate was set to 300 r / min, and the reaction was carried out for 6 h to obtain the mixtures.

[0042] All mixtures were transferred to a vacuum distillation apparatus. The stirring rate was set to 180 r / min throughout the distillation process, the vacuum level was maintained at -0.090 MPa, the distillation temperature was 60℃, and the maximum material temperature did not exceed 70℃. Distillation was stopped when the volume of distillate flowing out was less than 1 mL every 10 minutes and the total mass fraction of ethanol and acetic acid in the distillate was less than 0.5%, yielding three groups of crude catalysts. All three groups of crude catalysts were washed with n-hexane at a mass-to-volume ratio of 1:4 g / mL. Each wash was performed with a stirring rate of 250 r / min for 18 minutes, followed by 25 minutes of settling and separation. This washing process was repeated four times. The absorbance of the upper washing layer was measured using UV light at a wavelength of 211 nm; a absorbance below 0.02 was considered a complete wash. Vacuum drying was performed at a vacuum degree of -0.096 MPa and a drying temperature of 45°C. During the drying process, a trace amount of nitrogen was introduced to contact the material in the same direction. Samples were taken every 30 minutes. Drying was stopped when the residual mass fraction of n-hexane was below 0.1%. Three groups of imidazole-cobalt ionic liquid coordination catalysts with different molar ratios were obtained.

[0043] Evaluation of the oxidation performance of Fischer-Tropsch wax with different catalyst ratios:

[0044] Three catalyst groups were used for the Fischer-Tropsch wax oxidation reaction. During the melting stage of the Fischer-Tropsch wax, the stirring speed was 180 r / min, and the temperature was raised to 125℃ to achieve complete melting. Each catalyst group was then added at 0.04% of the Fischer-Tropsch wax mass, and the stirring speed was increased to 350 r / min for 12 min. Air treated with silica gel and activated carbon adsorption was introduced at a rate of 0.4 L of standard-condition air per kilogram of Fischer-Tropsch wax per minute. The system was heated at a rate of 1.5℃ / min, and the reaction temperature was controlled at 145℃ ± 2℃ for 4 h of stirring. After the reaction was completed, the air supply was stopped, and the mixture was cooled to 70℃ for crystallization. The crystals were centrifuged, and the oxidation products were collected. The acid value, ash content, and clay consumption of the products were measured.

[0045] Table 1

[0046] molar ratio product acid value Product ash White clay consumption 2.00:1 112.6 0.082 12.4 2.05:1 135.3 0.041 7.1 2.10:1 121.4 0.053 9.6

[0047] Based on the data analysis in Table 1: Under the condition of a molar ratio of 2.00:1, the relative proportion of cobalt acetate is relatively high, and some cobalt salts in the system cannot complete coordination bonding. Free cobalt components are introduced into the oxidation reaction system, resulting in increased ash content, increased consumption of bleaching clay, and a lower acid value level from Fischer-Tropsch wax oxidation. Under the condition of a molar ratio of 2.10:1, the proportion of imidazole bromide added increases, and some imidazole salts do not participate in the coordination reaction, leading to a decrease in the number of effective active sites on the catalyst surface, weakened catalytic activity, and a decrease in the acid value of the product. Under the condition of a molar ratio of 2.05:1, the coordination reaction proceeds to a higher degree, the catalyst can exert a better catalytic effect, the product acid value reaches the highest level among the three groups, and ash content and bleaching clay consumption are simultaneously at lower levels. Comparing the results of the three groups, a molar ratio of 2.05:1 for 1-dodecyl-3-methylimidazolium bromide and cobalt acetate is recommended for stage S1. Figure 2 As shown.

[0048] Example 3:

[0049] Optimization of the mass-to-volume ratio of crude catalyst to n-hexane in stage S3:

[0050] Catalyst washing and purification experiments under different solid-liquid ratios:

[0051] Multiple identical crude imidazole-cobalt ionic liquid coordination catalysts were prepared using the complete process S1 and S2 in Example 1. All parameters of the remaining steps in the catalyst preparation process were kept constant, except for the mass-to-volume ratio of the crude catalyst to n-hexane in S3. All three ratios were within the process setting range, with three experimental groups set at 1:3 g / mL, 1:4 g / mL, and 1:5 g / mL.

[0052] For each experiment, an equal amount of crude catalyst was taken and hexane solvent was added according to the corresponding mass-to-volume ratio. The stirring rate for each wash was 250 r / min, the stirring time was 18 min, and the settling time was 25 min. The washing operation was repeated four times. After each wash, the upper hexane washing liquid was collected, and the absorbance value was recorded at a wavelength of 211 nm using ultraviolet light. After washing, the material was transferred to a vacuum drying device. The vacuum degree during drying was not lower than -0.095 MPa, the drying temperature was 45℃, and a trace amount of nitrogen was continuously introduced during the drying stage. The nitrogen was in contact with the material in the same direction. Samples were taken every 30 min for testing. Drying was stopped when the residual mass fraction of hexane in the material was lower than 0.1%, resulting in three groups of finished catalysts treated with different solid-liquid ratios.

[0053] Verification of the oxidation performance of catalysts obtained with different washing solid-liquid ratios:

[0054] The three groups of catalysts obtained from washing were used to conduct Fischer-Tropsch wax oxidation experiments. Fischer-Tropsch wax was melted at 125℃, the catalyst dosage was 0.04% of the Fischer-Tropsch wax mass, the air flow rate was 0.4 L of standard air per minute per kilogram of Fischer-Tropsch wax, the reaction temperature was 145℃±2℃, and the reaction was stirred for 4 hours. After the reaction was completed, the product was collected, and the acid value, ash content, and clay consumption were measured.

[0055] Table 2

[0056] The mass-to-volume ratio of crude catalyst to n-hexane (g / mL) product acid value Product ash White clay consumption 1:3 118.2 0.076 11.7 1:4 134.7 0.043 7.3 1:5 126.5 0.040 8.8

[0057] Based on the data analysis in Table 2: Under a mass-to-volume ratio of 1:3 g / mL, the amount of solvent added in a single step is insufficient, resulting in inadequate mixing between the crude catalyst and n-hexane. This makes it difficult to remove free impurities trapped within the material, which then enter the subsequent oxidation reaction system, leading to increased ash content, increased consumption of bleaching clay, and interference with the catalytic reaction, resulting in a decrease in the acid value of the product. Under a mass-to-volume ratio of 1:5 g / mL, the solvent amount is sufficient, and the impurity elution effect is good. However, some catalyst components dissolve and disperse in the n-hexane solvent, causing catalyst loss, a decrease in the effective catalyst dosage, and a decline in the acid value of the oxidation product. Under a mass-to-volume ratio of 1:4 g / mL, the solvent amount ensures sufficient impurity elution, minimal catalyst dissolution loss, excellent acid value of the oxidation product, and ideal levels of ash content and bleaching clay consumption. Considering both the washing effect and catalyst loss, a mass-to-volume ratio of 1:4 g / mL for the crude catalyst to n-hexane in the S3 stage is selected.

[0058] Example 4:

[0059] Optimization of catalyst dosage in stage S4:

[0060] Fischer-Tropsch wax oxidation reaction under different catalyst dosages:

[0061] Imidazole-cobalt ionic liquid coordination catalyst was prepared according to the complete process of Example 1. The Fischer-Tropsch wax melting temperature in step S4 was kept constant at 125°C, and the stirring speed was 180 r / min during the Fischer-Tropsch wax melting stage. After the catalyst was added, the stirring speed was increased to 350 r / min, and the stirring time was 12 min. The introduced air was pre-treated by silica gel adsorption and activated carbon adsorption, and the air introduction rate was set to 0.4 L of standard air per kilogram of Fischer-Tropsch wax per minute. The system heating rate was 1.5°C / min, the reaction temperature was maintained at 145°C ± 2°C, and the reaction was stirred for 4 h. Only the catalyst-to-Fischer-Tropsch wax mass ratio was changed; all three addition amounts fell within the process limit range, and three experimental groups were set up with 0.02%, 0.04%, and 0.06% catalysts.

[0062] After each group of experimental reactions was completed, the air supply was stopped, and the system was cooled to 70°C for cooling crystallization. The catalyst and the Fischer-Tropsch wax oxidation product were separated by centrifugation. The Fischer-Tropsch wax oxidation product was collected, and the acid value, ash content, and clay consumption of each group of samples were determined.

[0063] Table 3

[0064] Catalyst dosage as a percentage of Fischer-Tropsch wax mass product acid value Product ash White clay consumption 0.02% 103.5 0.037 6.8 0.04% 135.1 0.042 7.2 0.06% 141.2 0.079 12.1

[0065] Based on the data analysis in Table 3: When the catalyst dosage is 0.02%, the number of catalytic active sites within the system is insufficient, the contact probability between Fischer-Tropsch wax and active sites is limited, the oxidation reaction is insufficient, and the product acid value is at a low level. When the catalyst dosage is 0.06%, the system has sufficient catalytic active sites, and the product acid value can be further improved. However, excess catalyst components cannot be completely recovered and separated, remaining in the product, directly causing a significant increase in product ash content and a substantial increase in bleaching clay consumption. Under the condition of a catalyst dosage of 0.04%, sufficient active sites can be provided to drive the oxidation of Fischer-Tropsch wax, resulting in a higher product acid value, while not introducing too many residual impurities, and keeping ash content and bleaching clay consumption at a low level. Considering the overall oxidation depth and product quality, the catalyst dosage for the S4 stage is determined to be 0.04% of the Fischer-Tropsch wax mass. Figure 3 As shown.

[0066] Example 5:

[0067] S4 stage air intake optimization:

[0068] Fischer-Tropsch wax oxidation experiments under different air flow conditions:

[0069] The imidazole-cobalt ionic liquid coordination catalyst prepared in Example 1 was used, with a catalyst dosage of 0.04% of the Fischer-Tropsch wax mass. The melting temperature of the Fischer-Tropsch wax was 125℃, and the stirring speed was 180 r / min during the melting stage. After the catalyst was added, the stirring speed was increased to 350 r / min and stirred for 12 min. The reaction temperature was controlled at 145℃±2℃, and the total reaction time was 4 h. The air was pretreated by silica gel adsorption and activated carbon adsorption, and the system heating rate was 1.5℃ / min. Only the air flow rate was changed, and all three flow rates were within the process range. Three experimental groups were set up: 0.3 L of standard air per kilogram of Fischer-Tropsch wax per minute, 0.4 L of standard air per kilogram of Fischer-Tropsch wax per minute, and 0.5 L of standard air per kilogram of Fischer-Tropsch wax per minute.

[0070] After the reaction was completed, the gas supply was stopped, the temperature was lowered to 70℃ for crystallization, centrifuged to separate the products, and the oxidized Fischer-Tropsch wax products were collected. The acid value, ash content, and clay consumption of each group of products were determined.

[0071] Table 4

[0072] Air flow rate (L / min) per kilogram of Fischer wax per minute product acid value Product ash White clay consumption 0.3 110.8 0.039 7.0 0.4 134.9 0.044 7.4 0.5 138.4 0.071 10.9

[0073] Based on the data analysis in Table 4: When the air flow rate is 0.3 L / kg Fischer-Tropsch wax per minute, the oxygen supply within the system is insufficient, and the oxidation reaction is limited by the oxygen concentration. Within the 4-hour reaction cycle, the oxidation conversion of Fischer-Tropsch wax is limited, and the product acid value is low. When the air flow rate is 0.5 L / kg Fischer-Tropsch wax per minute, the oxygen supply is sufficient, and the product acid value increases slightly. However, excessive air induces more side reactions, generating some polar byproducts, leading to increased ash content and significantly increased consumption of bleaching clay. Under the condition of an air flow rate of 0.4 L / kg Fischer-Tropsch wax per minute, the oxygen supply can match the consumption of the oxidation reaction, the main oxidation reaction dominates, the degree of side reactions is low, the product acid value is high, and ash content and bleaching clay consumption are controlled at ideal levels. Considering both the oxidation effect and the side reaction situation, the air flow rate for stage S4 is determined to be 0.4 L / kg standard state air per minute for each kilogram of Fischer-Tropsch wax. Figure 4 As shown.

[0074] Example 6:

[0075] Optimization of S5 stage cooling crystallization temperature:

[0076] Catalyst recovery experiments at different cooling crystallization temperatures:

[0077] The first round of Fischer-Tropsch wax oxidation reaction was completed using the complete process described in Example 1. The catalyst dosage was 0.04% of the Fischer-Tropsch wax mass, and the air flow rate was 0.4 L of standard-condition air per minute per kilogram of Fischer-Tropsch wax. The reaction temperature was 145℃±2℃, and the reaction time was 4 hours. After the reaction, the air flow was stopped, and all other post-treatment operations remained unchanged, except for the cooling and crystallization temperature. All three temperatures were within the process range, with experiments conducted at 60℃, 70℃, and 80℃.

[0078] The system was cooled to its corresponding crystallization temperature and then kept at a constant temperature to fully complete the crystallization process. Centrifugation was then performed to separate the catalyst from the raw materials. The recovered catalyst was dried at 90°C, and the mass of each recovered catalyst group was weighed to calculate the catalyst recovery efficiency. Simultaneously, the Fischer-Tropsch wax oxidation product after centrifugation was collected, and its acid value and ash content were determined. The recovered and dried catalyst was directly fed into the second round of oxidation reaction, and the acid value of the second round oxidation product was recorded.

[0079] Table 5

[0080] Cooling crystallization temperature (°C) Catalyst recovery efficiency % Acid value of the first batch of products Acid value of second-round products 60 78.3 133.6 105.2 70 92.7 134.8 126.4 80 84.1 122.5 127.1

[0081] Based on the data analysis in Table 5: When the cooling crystallization temperature is 60℃, the overall viscosity of the material is high, and some wax coating is present on the surface of the catalyst particles. This leads to significant catalyst loss during centrifugation, resulting in low catalyst recovery efficiency. The wax coating on the catalyst surface also covers the active sites, causing a significant decrease in the acid value of the product in the second round of reaction. At a cooling crystallization temperature of 80℃, the material viscosity decreases, improving the sedimentation ability of the catalyst particles and resulting in a higher catalyst recovery efficiency than at 60℃. However, some Fischer-Tropsch oxidized wax components remain liquid at this temperature and are lost with the filtrate during centrifugation, directly causing a decrease in the acid value of the first-round product. At a cooling crystallization temperature of 70℃, the material viscosity is at a suitable level, allowing for sufficient sedimentation and separation of the catalyst particles. This results in a higher catalyst recovery efficiency, less loss of Fischer-Tropsch oxidized wax, a higher acid value in the first-round product, and the recovered catalyst maintaining good catalytic activity in the second round of reaction. Considering the catalyst recovery efficiency, product loss, and the secondary reaction performance of the recovered catalyst, 70℃ is selected as the cooling crystallization temperature for stage S5. Figure 5 As shown.

[0082] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A method for preparing a catalyst for the Fischer-Tropsch wax oxidation reaction, characterized in that, The specific steps of this method are as follows: S1. Dissolve 1-dodecyl-3-methylimidazolium bromide in anhydrous ethanol. Under nitrogen protection, add cobalt acetate in batches according to a molar ratio of 1-dodecyl-3-methylimidazolium bromide to cobalt acetate of 2.05:

1. Maintain the system under a slightly positive pressure throughout the reaction process and stir at 55~65℃ for 4~8 hours to obtain a mixture. S2. The mixture is subjected to vacuum distillation at -0.085~-0.095MPa and 55~65℃ to obtain a crude imidazole-cobalt ion liquid coordination catalyst. S3. Add n-hexane to the crude catalyst for washing and separation, repeat washing until the UV detection endpoint, and dry at 40~50℃ to obtain imidazole-cobalt ion liquid coordination catalyst. S4. Melt Fischer-Tropsch wax at 120~130℃, add the catalyst at 0.02~0.06% of the mass of Fischer-Tropsch wax, introduce air under stirring, and react at 140~150℃ for 3~5 hours; S5. After the reaction is complete, stop the gas supply, cool down to crystallize, and centrifuge to recover the catalyst. Dry the recovered catalyst and reuse it for subsequent oxidation reactions.

2. The method for preparing the catalyst for the Fischer-Tropsch wax oxidation reaction according to claim 1, characterized in that, In step S1, during the dissolution stage of 1-dodecyl-3-methylimidazolium bromide, 800-1000 mL of anhydrous ethanol is added per mole of 1-dodecyl-3-methylimidazolium bromide, the stirring rate is set to 200-300 r / min, and the stirring time is 20-30 min. The cobalt acetate is added to the system in 3 to 5 batches, with an interval of 5-8 min between adjacent additions. The system heating rate is controlled at 2-3 °C / min, and the stirring rate during the isothermal reaction stage is set to 250-350 r / min.

3. The method for preparing the catalyst for the Fischer-Tropsch wax oxidation reaction according to claim 1, characterized in that, The nitrogen protection system maintains a slightly positive pressure, with a pressure range of 0.01~0.03MPa, a nitrogen flow rate of 0.5L / min, and a nitrogen purging operation lasting 15min.

4. The method for preparing the catalyst for the Fischer-Tropsch wax oxidation reaction according to claim 1, characterized in that, In step S2, the stirring rate during the entire vacuum distillation process is set to 150-200 r / min; vacuum distillation is terminated when the volume of distillate flowing out every 10 minutes is less than 1 mL and the total mass fraction of ethanol and acetic acid in the distillate is less than 0.5%; the maximum temperature of the material during the vacuum distillation process does not exceed 70℃.

5. The method for preparing the catalyst for the Fischer-Tropsch wax oxidation reaction according to claim 1, characterized in that, In step S3, the crude catalyst and n-hexane are fed at a mass-to-volume ratio of 1:3 to 1:5 g / mL; the stirring rate for each wash is 200 to 300 r / min, the stirring time is 15 to 20 min, and the settling time is 20 to 30 min; the washing operation is repeated 3 to 5 times, and the ultraviolet detection signal is collected at a wavelength of 211 nm. The washing endpoint is determined when the absorbance is lower than 0.02; the vacuum degree during the drying process is not lower than -0.095 MPa, and samples are taken every 30 min. The drying process ends when the residual mass fraction of n-hexane in the material is lower than 0.1%.

6. The method for preparing the catalyst for the Fischer-Tropsch wax oxidation reaction according to claim 1, characterized in that, In step S3, a small amount of nitrogen is continuously introduced during the drying stage, and the nitrogen comes into contact with the material in the same direction.

7. The method for preparing the catalyst for the Fischer-Tropsch wax oxidation reaction according to claim 1, characterized in that, In step S4, the stirring speed during the Fischer-Tropsch wax melting stage is set to 150-200 r / min; after the catalyst is fed, the stirring speed is increased to 300-400 r / min, and the stirring time is 10-15 min; the introduced air is treated by silica gel adsorption and activated carbon adsorption in sequence. The air flow rate is 0.3~0.5L of standard air per minute per kilogram of Fischer-Tropsch wax; the system heating rate is 1~2℃ / min; and the reaction temperature fluctuation range is 145℃±2℃.

8. The method for preparing the catalyst for the Fischer-Tropsch wax oxidation reaction according to claim 1, characterized in that, In step S5, the cooling crystallization operation temperature is controlled at 60~80℃; the drying temperature of the recovered catalyst is not higher than 100℃.

9. The method for preparing the catalyst for the Fischer-Tropsch wax oxidation reaction according to claim 1, characterized in that, In step S5, the recovered catalyst is used for subsequent multiple rounds of repeated oxidation reactions, and product samples are collected periodically to record the acid value, ash content, and clay consumption values ​​of each round of samples in order to monitor catalyst activity.

10. The application of the method for preparing the catalyst for the Fischer-Tropsch wax oxidation reaction according to any one of claims 1-9, characterized in that, This method is applied to the oxidation of Fischer-Tropsch wax to prepare oxidized Fischer-Tropsch wax products.